Developments in Eu+2‐Doped Strontium Aluminate and Polymer/Strontium Aluminate Composite. Issue 1 (4th June 2014) - Anesh, M. P.; Gulrez, Syed K. H.; Anis, A.; Shaikh, H.; Ali Mohsin, M. E.; AL‐Zahrani, S. M.
ABSTRACT The discovery of rare earth based phosphors in 1960s started a new era of luminescence. In comparison with sulfide‐based phosphors, strontium aluminates received worldwide acceptance because of their chemical stability and good luminescent properties. The SrAlxOy:Eu2+, Dy3+ phosphors excited by UV or visible light emit phosphorescence in the blue‐green region after the excitation source has been removed, and the phosphorescence last for more than 15 h. The major disadvantage of SrAlxOy:Eu2+, Dy3+ phosphors is that they are prone to hydrolysis and their luminescent properties gradually deteriorate. The dispersion of these phosphors in a waterproof polymer matrix is an alternative method reported for retaining their luminescent properties. The review extensively deals with strontium aluminate based luminescent materials, the mechanism of luminescence, their synthesis techniques, and different mixing procedures to prepare polymer/strontium aluminate composites. Different methods to improve the dispersion of the strontium aluminate in the polymer matrix are also outlined.